(untitled) (International Journal of Nursing Education, 2023)
Introduction : Surgery is almost always viewed as a life crisis and evokes anxiety and fear . In line with the growing number of surgical procedures being performed worldwide, postoperative complications are also increasing, proportionately increasing mortality, impairing patients’ postoperative outcome, lengthening intensive care and total hospital stay. Preoperative assessment and care is extremely important prior to any invasive procedure including minor and major surgical procedures. Physical and psychological preparation tends to improve surgical outcomes. Preoperative teaching provides with pertinent information concerning the surgical process and the intended surgical procedure as well as anticipated patient behavior (anxiety, fear), expected sensation, and the probable outcomes. The experimental study was conducted to assess the effectiveness of nursing protocol on postoperative outcome among patients undergoing major visceral surgeries in a selected tertiary care hospital. The objectives of the study were to assess the post operative outcome of patients undergoing major visceral surgeries in the study and control group, to determine the effectiveness of nursing protocol on postoperative outcome among patients undergoing major visceral surgeries and to associate the post operative outcome with the socio demographic variables. Materials and Methods: An experimental, post-test only design was used to conduct the study at tertiary care hospital in Delhi. The intervention was carried out in the pre-operative surgical wards of the tertiary care hospital and post-operative data was collected in the inpatient surgical unit. 63 samples in the experimental group and 63 samples in the control group were selected by simple random sampling technique. The study revealed that there was a significant difference in the pain scores on the seventh day after surgery and on the patient satisfaction related to preoperative education and intraoperative care.